How to Manage a Failed Cartilage Repair: A Systematic Literature Review - Rosa, Donato; Di Donato, Sigismondo Luca; Balato, Giovanni; D'Addona, Alessio; Smeraglia, Francesco; Correra, Gaetano; Di Vico, Gianni (Joints, 2017)
Purpose The aims of this paper are to report the rate and risk factors for the failure of the most common cartilage repair technique, and analyze the most important factors that could influence the choice of a specific surgical treatment to revise a failed cartilage repair.Methods A review of the literature was performed focusing on failed cartilage repair and related treatments. Two of the authors independently screened articles. Conflicts about the inclusion of a paper was resolved by further evaluation by the senior author. Review articles, articles written in languages different from/other than English, case reports, and papers that did not evaluate the outcomes of interest were excluded. Full-text version of each included paper was obtained and relevant data were extracted and collected in a database.Results At the end of the screening process, 31 articles were included. Microfractures and mosaicplasty showed a nonnegligible failure rate at short- and midterm. Better results, especially in terms of time to failure or revision, were reported with the use of autologous chondrocyte implantation (ACI) and osteochondral allograft (OCA) transplantation. Regarding the treatment of failed cartilage repair, the use of OCA transplantation in patients with previous failed cartilage repair may be a safe option. The revision of failed OCA transplantation with further OCA seems to have a greater failure rate. Patients with previous failed ACI or matrix-induced autologous chondrocyte implantation (MACI) who underwent further MACI or ACI reported acceptable results. Otherwise, ACI in patients with history of previous subchondral marrow stimulation (SMS) demonstrated a greater failure rate.Conclusion From the analysis of the literature, OCA transplantation seems to be the most reliable treatment of a failed SMS. ACI or MACI showed acceptable results in patients with previously failed MACI or ACI.Level of Evidence Level IV, systematic review of level I-IV studies.
Keywords: cartilage; repair; failure; revision; surgery